The Effect Of Board Diversity And Green Intellectual Capital On Financial Sustainability With Csr As A Moderating Variable (Empirical Study On Energy Companies For The Period 2020-2024) - ayu lestari; Siti Kustinah (LP2M IAIN Palopo, 2026)
With corporate social responsibility (CSR) acting as a moderating variable, this study attempts to examine the impact of board diversity and green intellectual capital on financial sustainability. The growing need for sustainability and good corporate governance, especially in businesses in the energy industry, is what spurred this study. Using secondary data from the annual reports and sustainability reports of energy sector businesses listed on the Indonesia Stock Exchange between 2020 - 2024, the study takes a quantitative approach. Gender, age, and educational background variety are used to gauge board diversity. Moderated Regression Analysis (MRA) is used to investigate the moderating function of CSR, whereas multiple regression analysis is used to look at the direct effects among factors. The findings suggest that financial sustainability is influenced by board diversity and green intellectual capital. Additionally, CSR improves the connection between financial sustainability and green intellectual capital, but its moderating influence on board diversity yields contradictory findings. It is anticipated that this research will offer theoretical insights and useful recommendations for developing businesses long-term financial sustainability plans.